IMPLEMENTATION OF THE ZONING SYSTEM POLICY FOR NEW STUDENT ADMISSIONS (PPDB) PUBLIC SENIOR HIGH SCHOOL LEVEL FOR THE 2021/2022 ACADEMIC YEAR IN BANGKA DISTRICT BANGKA BELITUNG ISLAND PROVINCE - Prihatini, Juliati; Bakuda, Destya Novinka; Agung, Efraim Putra (Jurnal Kebijakan Pemerintahan, 2024)
Abstract New Student Admission (PPDB) with a zoning system is a policy that prioritizes the distance between prospective students' homes and schools, not school exam scores. There are still problems related to this policy, so the authors need to conduct research related to this policy. The purpose of this study was to find out and analyze how the implementation of the PPDB zoning system policy for public high schools in Sungailiat and Pemali Districts, Bangka Regency for the 2021/2022 academic year, the inhibiting and supporting factors, and the efforts made to overcome these obstacles. The research method used is descriptive qualitative research method. Data collection techniques used are interviews, observation, and documentation. The number of informants in this study were 20 people, using purposive sampling technique. The results of this study indicate that the implementation of the PPDB zoning system policy at the State High School level for the 2021/2022 academic year is good, but not optimal, this can be seen from the existing indicators. have not been achieved. The inhibiting factors for this policy include the delay in ratifying technical guidelines, the accuracy of the application of distance measurements, the existence of wedges in the division of zoning areas, friction of interests, the absence of binding legal rules in the event of deviations. violations in its implementation, the public does not understand the online system used. Factors supporting this policy are available financial support, good coordination between the Education Office and education units, and a good understanding of implementing officials regarding zoning system policies. Efforts made by the local government include conducting technical evaluation and housing for prospective students, outreach to the community about the division of zoning areas, providing additional seats for outstanding students, giving strict sanctions such as for students who violate sanctions, providing continuing education. and socialization. to the local community. Keywords: new student admission, policy implementation, zoning system